Determinan Tingkat Pengangguran Terbuka di Kabupaten/Kota Provinsi Jawa Barat Tahun 2019-2023 - Dilla Andini; Reikha Habibah Yusfi (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2025)
Indonesia is one of the developing countries that cannot be separated from the problem of unemployment, the number of residents who have increased every year has an unfavorable impact if not balanced with quality. The increase in population must be balanced with the quality and ability of each workforce. The average Open Unemployment Rate (TPT) in Indonesia has decreased every year, but the problem of unemployment is still the center of attention. Java Island has a higher population density and is still a favorite place for migrants to find work. West Java Province is among the five provinces with the highest TPT in Indonesia. The purpose of this study is to identify the factors that cause the existing problems and determine the variables that can be used to solve the problem of high unemployment in the districts/cities of West Java Province. This research uses multiple linear regression analysis method. The results of this study indicate that the variables of Economic Growth (PE) and Labor Force Participation Rate (TPAK) have a negative and significant influence on the TPT in the district / city of West Java Province. Simultaneously, the variables of economic growth, TPAK, MSE and HLS affect the TPT in the districts/cities of West Java Province. The coefficient of determination (R2) of this research model is 0.8693 or equivalent to 86.93%. Independent variables consisting of PE, TPAK, MSE, and HLS are able to explain the TPT variable in the district / city of West Java Province by 86.93%. While 13.07% is explained by other variables that are not explained in the study.